(untitled) (Titivillus, 2025)
Los escudos grabados fueron sumamente habituales en los libros impresos en la Ciudad de México en el periodo virreinal. En este trabajo haremos una primera aproximación a las funciones que tenían y estableceremos una categorización. Woodcut and engraved coats of arms were ubiquitous in books printed in Mexico City during the viceregal period. In this article we make a preliminary assessment of their function and categorize them.